1999
DOI: 10.2337/diabetes.48.4.766
|View full text |Cite
|
Sign up to set email alerts
|

Free fatty acids impair hepatic insulin extraction in vivo.

Abstract: Hyperinsulinemia is a common finding in obesity and results from insulin hypersecretion and impaired hepatic insulin extraction. In vitro studies have shown that free fatty acids (FFAs), which are often elevated in obesity, can impair insulin binding and degradation in isolated rat hepatocytes. To investigate whether FFAs impair hepatic insulin extraction (E(H)) in vivo, either saline (SAL) or 10% Intralipid (0.03 ml x kg(-1) x min(-1)) plus heparin (0.44 U x kg(-1) x min(-1)) (IH) was infused into normal dogs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
98
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(112 citation statements)
references
References 52 publications
13
98
1
Order By: Relevance
“…The effect is opposite to that expected from a study in normal dogs that concluded that FA impair hepatic clearance of insulin (36). Differences in experimental design and species differences, as well as the presence of diabetes in our study, could be important for the discrepancy.…”
Section: Discussioncontrasting
confidence: 99%
“…The effect is opposite to that expected from a study in normal dogs that concluded that FA impair hepatic clearance of insulin (36). Differences in experimental design and species differences, as well as the presence of diabetes in our study, could be important for the discrepancy.…”
Section: Discussioncontrasting
confidence: 99%
“…No such differences in the C-peptide or calculated insulin secretion rate AUC were noted. The most likely explanation for this finding is a NEFA-mediated reduction of insulin extraction by the liver [28]. Although insulin extraction by the liver seems to be constant throughout the physiological range of insulin concentration at steady state insulin concentrations [29,30], it declines during dynamic (non steady state) conditions and in the presence of very high insulin concentrations, similar to those seen in our study during the second bolus infusion of arginine [31±33].…”
Section: Discussionsupporting
confidence: 79%
“…A direct stimulatory effect of fatty acids upon islets provides a plausible explanation for the greater insulinotropic effect with increased NEFA concentrations, as seen in this study, although in vivo, other factors, such as insulin sensitivity, hepatic insulin clearance and other stimulants have to be considered. There is evidence that both insulin sensitivity [13] and hepatic insulin clearance [9] are reduced after a short-term increase of total plasma NEFA concentrations, but it is not clear if there is a difference between the types of fatty acid. It has been reported that the insulin resistance induced by an acute increase (90 min) of plasma NEFA concentrations was precisely countered by a fatty acid-induced increase in insulin secretion [13].…”
Section: Discussionmentioning
confidence: 99%
“…Increased plasma NEFA concentrations can have adverse effects on various tissues. Excess plasma NEFA concentrations can lead to a reduced skeletal muscle glucose uptake and oxidation [4,5,6], increased hepatic glucose output [7] and a decrease in hepatic insulin clearance [8,9]. These mechanisms could lead to glucose intolerance and insulin resistance leading to Type II diabetes.…”
mentioning
confidence: 99%